International Financial Flows and Transactions Taxes : Survey and Options - Spahn, P. (IMF Working Papers; Working Paper, 1995)
Tobin has suggested that exchange rate volatility be controlled through a tax on international financial transactions. This analysis shows that the Tobin tax as a pure transaction tax is not viable. The tax would impair financial operations and create international liquidity problems. It is also unlikely to deter speculation. However, a possible alternative would be a two-tier rate structure-consisting of a low-rate transaction tax plus an exchange surcharge. The exchange rate could move freely within a 'crawling' exchange rate band, but overshooting the band would trigger a tax on an 'externality,' which is the discrepancy between the market exchange rate and the closest margin of the band. The scheme is inspired by the European Monetary System. However, exchange rates would be kept within the target range through a tax, not through interest policy or central bank sterilization and, eventually, the depletion of international reserves.